Hierarchical parcel distribution facility ground network design problem. (2nd November 2010) - Ben-Ayed, Omar
This paper is concerned with the network design problem for parcel ground distribution facilities. The design involves three interacting levels of facilities in addition to customers, with each lower level being assigned to exactly one higher level. The link cost, depending on the transportation mode, is expressed as a function of the link load, which is determined by the assignment variables. The resulting model is a complex integer program with non-linear objective function. The model is solved by a heuristic method where the lower-level solution provides input data for the higher-level one. The method is illustrated with an example based on a real world application.